Second Five Year Plan: Education & Social Services - Planning Commission, Government of India (Planning Commission, Government of India, 1956)
The system of education has a determining influence on the rate at which economic progress is achieved and the benefits which can be derived from it. Economic development naturally makes growing demands on human resources and in a democratic set-up it calls for values and attitudes in the building up of which the quality of education is an important element. The socialist pattern of society assumes widespread participation of the people in all activities and constructive leadership at various levels.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Second Five Year Plan- Education & Social Services; Health; Scientific and Technological Research